DOI: 10.22215/etd/2007-08443
|View full text |Cite
|
Sign up to set email alerts
|

Soot emissions from turbulent diffusion flames burning simple alkane fuels

Abstract: The author has granted a non exclusive license allowing Library and Archives Canada to reproduce, publish, archive, preserve, conserve, communicate to the public by telecommunication or on the Internet, loan, distribute and sell theses worldwide, for commercial or non commercial purposes, in microform, paper, electronic and/or any other formats. AVIS: L'auteur a accorde une licence non exclusive permettant a la Bibliotheque et Archives Canada de reproduire, publier, archiver, sauvegarder, conserver, transmettr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The Carleton lab-scale flare facility was designed and built to increase the experimental scale of the work accomplished by Canteenwalla (2007) and McEwen (2010) using a smaller-scale experiment housed at the National Research Council of Canada.…”
Section: Chapter 2 Experimental Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…The Carleton lab-scale flare facility was designed and built to increase the experimental scale of the work accomplished by Canteenwalla (2007) and McEwen (2010) using a smaller-scale experiment housed at the National Research Council of Canada.…”
Section: Chapter 2 Experimental Setupmentioning
confidence: 99%
“…These components include: the modular turbulent diffusion burner, the fuel delivery system, the various flare gas compositions tested, the controllable exhaust system, the experimental analysis instrumentation, and the flame imaging equipment. The turbulent diffusion burner was previously used in the work of Canteenwalla (2007) and McEwen (2010) and will be discussed within that context in Section 2.1. Section 2.2 discusses the fuel delivery system and provides details of all components upstream of the burner including the mass flow controllers, gas storage and handling, and other related components.…”
Section: Chapter 2 Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…These works yield values of E{m) x in the range of 0.21 to 0.42. Canteenwalla (2007) summarized available data published in the literature and calculated the mean and standard error for E(m) x of 0.32 ± 0.01 assuming E(m) x to be independent of wavelength, which is a common assumption when using E(m) A in the visible and near infrared (Krishnan et al, 2000). However, most recently, Thomson et al (2008b) applied a spectrally resolved LOSA diagnostic (Spec-LOSA) to an ethylene/air flame in the wavelength range of 450 to 950 nm and observed that there is significant decrease of the absorption function with increasing wavelength.…”
mentioning
confidence: 99%